Language Performance of an Eight-Year-Old Child with Speech Delay - Okitasari, Indah; Sukma, Bayu Permana; Hendrastuti, Retno Hendrastuti; Lestariningsih, Dewi Nastiti; Ramadini, Febyasti Davela (Journal of Languages and Language Teaching, 2023)
Language development begins at the beginning of human life, but the stages are diverse. This study aimed at describing an 8 year old child speech delay and identifying the causes of the delay and its relation to language performance at school. A case study design encountered that AA could not speak clearly especially, and a hearer did not understand what she said except her mom. For almost one semester, the researchers tried to observe AA's speech pattern and found some speech error-unclear saying words containing H and Z, and X at the beginning and the end of the word. Often the researchers found her emotional when she was not able to perceive and deliver her feelings through words. Parents’ roles and background in the interview transcripts have also been one reason why AA got worse in speaking. However, the language subject result in the AA report book was not poor. The teacher had an alternative language learning to motivate The child to perform her best. Parent support is needed more as AA is under teacher supervision to learn in a higher class.